2017
DOI: 10.1108/ebhrm-08-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Facets of job satisfaction and work engagement

Abstract: Purpose The purpose of this paper is to analyze the relationship between the facets of job satisfaction and the work engagement. Previous studies that focus on the linkages between work engagement and overall job satisfaction ignore the multi-faceted nature of job satisfaction construct. In this study, how job satisfaction facets are linked to three dimensions of work engagement – i.e. vigor, dedication and absorption – is discussed by drawing on the social exchange theory. Design/methodology/approach The cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 84 publications
(166 reference statements)
9
62
0
9
Order By: Relevance
“…As already suggested, the facet organization and management in PAJS-FI should be further investigated as Cronbach’s alpha dropped when including the facet-item. Work engagement seems to have much in common with JS [48]. Here, also the correlational structure for PAJS and PAJS-FI remained the same: the higher work engagement was, the higher was JS.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As already suggested, the facet organization and management in PAJS-FI should be further investigated as Cronbach’s alpha dropped when including the facet-item. Work engagement seems to have much in common with JS [48]. Here, also the correlational structure for PAJS and PAJS-FI remained the same: the higher work engagement was, the higher was JS.…”
Section: Discussionmentioning
confidence: 61%
“…The importance of work engagement for todays’ work environment has been proved in many studies [13]. Different facets of JS are meant to make different predictions of work engagement, e.g., satisfaction with the work by itself is the key driver of work engagement, whereas satisfaction with payment is not linked to work engagement [48]. …”
Section: Introductionmentioning
confidence: 99%
“…This study confirms the findings of previous research that there is a positive relationship between job satisfaction and work engagement. Yalabik et al (2017), in a study with banking specialists concluded that both intrinsic and extrinsic job satisfaction are linked to work engagement; emphasizing that when workers are satisfied with the job, they are fully engaged at work. Overall, intrinsic job satisfaction had a stronger positive correlation with work engagement when compared to extrinsic job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Work engagement is beneficial to the organization and the employee, both at work and outside of work (Seppälä, Mauno, Feldt, Hakanen, Kinnunen, Tolvanen, & Schaufeli, 2009). Work engagement has been found to be a predictor of turnover intention and an antecedent (Abraham, 2012) and outcome of job satisfaction (Yalabik, Rayton, & Rapti, 2017); therefore emphasizing the need for supervisor support, fair and sound company policies and procedures, and a job that is challenging is important (Abraham, 2012). Engaged individuals are immersed in their work roles and are less likely to leave the job (Khan, 1990).…”
Section: Work Engagementmentioning
confidence: 99%
“…These results indicate that the high and low of innovative behavior is largely determined by the relationship of work that grows in the personal education staff. The theoretical findings above which state working work relationship directly influence innovative behavior are explained by Yalabik, Rayton, and Rapti, engaged employees show more personal initiative and innovative work behavior [37]. They tend to be more involved and socially connected to their work, which allows more opportunity to contribute to improvement and innovation.…”
Section: B Discussionmentioning
confidence: 98%